MANAGING GREEN ARCHITECTURE THROUGH LIFE STYLE - Titien Saraswati (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2013)
Anywhere in the world, whether in rural or urban area, we cannot avoid the issue of global warming. In the urban area, about 80% of our activities are inside the buildings: in the houses, schools, offices, manufacture buildings, hotels, etcetera. Only a few of our activities take place outside the buildings. The conditions inside the buildings for our activities are far from comfort right now. In other words: our activities inside the buildings need some devices to help us to support the activities running well. In fact, some devices to support our activities generally exploit our natural resources and energies that in turn, degrade our environment.There are also some statements that the efforts to fight degrading environment are the domain of the government only. In fact, the efforts to fight degrading environment are our business, the responsibility of all people. “Green” now is the popular word for us, and the new trend for our daily living. Whereas, this is not a new trending topic in our life, but this must be the change in our life style. That is, the need for architectural design, specifically architectural engineering that green enough for the condition of the earth, the changing climate, and degrading environment; need the changing life style.The objective of this paper is to explore the possible things to manage green architecture through green life style. The methods used by examining life style that contributes to green architecture. The conclusion is that some simple life styles can have influencing factors to green architecture.